Assessment of the impact of COVID-19 on the hearing organ - Jan Piotrowski; Bianka Nowińska; Izabela Hądzlik (Family Medicine & Primary Care Review)
Otologic dysfunctions are an unusual manifestation of COVID-19 infection. Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a probable etiological agent of hearing organ dysfunction, including sudden sensorineural hearing loss (SSNHL). Among other otologic dysfunctions associated with COVID-19 are mild to profound, unilateral and bilateral hearing impairment, complete permanent deafness, tinnitus and otalgia. Otologic symptoms may coexist with other COVID-19 infection symptoms or may be an isolated manifestation of the disease. Pure tone audiometry, otoacoustic emission (OAE) and MRI are used to make a diagnosis. Treatment options include administration of steroids and intratympanic injections of triamcinolone. However, in most patients, the initiation of treatment was not required. In these patients, audiological control was sufficient. Additionally, drugs included in COVID-19 treatment regimens and administrated in intensive care units (ICU), such as chloroquine, hydroxychloroquine, azithromycin and furosemide, may be the cause of hearing impairment, due to their potential ototoxic effect. The following review article describes COVID-positive patients with diagnosed otologic dysfunctions. The aim of this article is to raise awareness that otologic symptoms may be the only clinical presentation of COVID-19, which is important due to early identification, administration of treatment and screening for hearing loss in patients who had suffered from COVID-19.